Top–Down Modulation on the Perception and Categorization of Identical Pitch Contours in Speech and Music - Weidema, Joey L.; Roncaglia-Denissen, M. P.; Honing, Henkjan (Frontiers in Psychology, 2016)
Whether pitch in language and music is governed by domain-specific or domain-general cognitive mechanisms is contentiously debated. The aim of the present study was to investigate whether mechanisms governing pitch contour perception operate differently when pitch information is interpreted as either speech or music. By modulating listening mode, this study aspired to demonstrate that pitch contour perception relies on domain-specific cognitive mechanisms, which are regulated by top-down influences from language and music. Three groups of participants (Mandarin speakers, Dutch speaking non-musicians, and Dutch musicians) were exposed to identical pitch contours, and tested on their ability to identify these contours in a language and musical context. Stimuli consisted of disyllabic words spoken in Mandarin, and melodic tonal analogues, embedded in a linguistic and melodic carrier phrase, respectively. Participants classified identical pitch contours as significantly different depending on listening mode. Top-down influences from language appeared to alter the perception of pitch contour in speakers of Mandarin. This was not the case for non-musician speakers of Dutch. Moreover, this effect was lacking in Dutch speaking musicians. The classification patterns of pitch contours in language and music seem to suggest that domain-specific categorization is modulated by top-down influences from language and music.